ANALISIS PENGARUH NILAITUKAR RUPIAH, TINGKAT SUKU BUNGA SBI DAN LAJU INFLASI TERHADAP INDEKS HARGA SAHAM PROPERTY (Studi pada Bursa Efek Indonesia periode 2008-2011) - I Gusti Ngurah Ketut Suka Wijaya (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
The growth of the national economy is currently in dire need of special attention and even the government needs to seriously address the issue of various economic and non-economic sectors. One of the main sources of external funding for alternative financing is favorable capital market. Likewise, the property company that went public in the Indonesia Stock Exchange always consider factors such as the dollar exchange rate tehadap, SBI and inflation in an effort to boost the stock price index in the market. The problems that can be formulated in this study is: How does the exchange rate against the dollar affect the stock price index in IDX property sector, how interest rates affect the stock price index in IDX property sector and how inflation affects the stock price index in IDX property sector ? Based on the results of the analysis can be concluded: 1) From the analysis of structural equation partially through SEM showed that after modifications to model 1, have obtained a better model than the main model because it has met six of the eight criteria of Goodness of Fit, the Chi-square , Probability, RMSEA, GFI, TLI, and CFI as well as two criteria considered marginal, the AGFI and DF. 2) The rupiah exchange rate has a positive and significant impact on stock price index of 0.158, which means the better the exchange rate, the higher the stock price index, property, and vice versa. 3) The interest rate SBI has a positive and significant impact on stock price index of 0.108, which means the better the SBI rate, the higher the stock price index, property, and vice versa. 4) The rate of inflation has a positive and significant impact on stock price index of 2.414, which means the better the inflation, the higher the stock price index, property, and vice versa.